2014
DOI: 10.1080/13572334.2014.939562
|View full text |Cite
|
Sign up to set email alerts
|

Government–Opposition Dynamics during the Economic Crisis in Greece

Abstract: The paper examines the turbulent period of 2010-2012 when Greece became the first EU member-state to accept the IMF/EU bailout package. Unarguably, accepting the bailout package did not have only economic but also electoral consequences as the established party system has been steadily disintegrating. We focus on the relationship between government and opposition parties and MPs in the legislature and we examine their voting behaviour during key economic bills during this period. We find that their behaviour c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…A closer look at this case shows that majoritarian electoral rules, which provide a 50 seat bonus to the first party, played a significant role in securing Government's support in Parliament. This is consistent with analyses of this reform that showed that there was not much resistance in Parliament to support this package (Gemenis and Nezi 2015).…”
Section: Table 3 Heresupporting
confidence: 86%
“…A closer look at this case shows that majoritarian electoral rules, which provide a 50 seat bonus to the first party, played a significant role in securing Government's support in Parliament. This is consistent with analyses of this reform that showed that there was not much resistance in Parliament to support this package (Gemenis and Nezi 2015).…”
Section: Table 3 Heresupporting
confidence: 86%
“…This changed with the signing of the MoU and the austerity measures imposed. At the beginning of the crisis, like the leaders at the EU level, who failed to agree on a European course of action, the leaders of established Greek parties failed to reach consensus on the national course of action; namely, to unify behind the MoU's programme or agree on an alternative path (Gemenis and Nezi, 2015). Unlike Portugal or Ireland (Mair, 2013), the major players of the Greek political scene, PASOK and ND, initially represented opposing sides of the MoU debate, enhancing its politicization.…”
Section: A New Division Line?mentioning
confidence: 99%
“…Antonis Samaras's NDthe centre-right 'pillar' of the party systemexhibited strong nationalist (and some populist) characteristics between the election of 2009 and its collaboration with PASOK in 2011. In that period, ND castigated PASOK's policies regarding the administration of the crisisespecially its decision to sign the so-called 'memorandum' (the written agreement between Greece and its lenders regarding the first bailout package, signed on May 2010)and tried to articulate an alternative (see Gemenis and Nezi, 2015;Vasilopoulou et al, 2013). It is crucial to stress, however, that ND's opposition to PASOK up until their collaboration was mostly based on moralistic arguments, stressing that 'the memorandum was unnecessarily humiliating' for the Greek nation (Gemenis and Nezi, 2015: 22).…”
Section: Enter Crisis: Reactivating the Populism/anti-populism Dividementioning
confidence: 99%